Teachers’ Perceptions of AI Classroom Management Tools for Enhancing Personalization and Academic Engagement of Secondary School Students in Ilorin - Temitayo Omolara Babalola; Abubakar Usman; Samuel Adenubi Onasanya; E. P. Fasina (WISE Pendidikan Indonesia, 2025)
The integration of Artificial Intelligence (AI) tools in classroom management is increasingly reshaping instructional practices, particularly in secondary schools. This study investigated the perceptions of teachers in Ilorin, Nigeria, regarding the effectiveness of AI classroom management tools in enhancing academic engagement. It also examined how these tools influence student engagement, support personalized instruction, and the challenges encountered in their use. Guided by the Technological Pedagogical Content Knowledge (TPACK) framework and the Diffusion of Innovations (DOI) theory, the study adopted a descriptive survey design. Data were collected from 150 secondary school teachers using a structured questionnaire and analyzed using descriptive statistics of mean and standard deviation. Findings show that teachers perceive AI tools as effective for engagement and personalized learning. However, concerns about inadequate technical skills, inconsistent infrastructure, and data privacy emerged as significant barriers to adoption. The study further found that while AI tools can enhance differentiated instruction and streamline classroom management, their integration remains limited by teachers’ confidence and institutional readiness. Based on these findings, the study recommends targeted, context-sensitive teacher training, improved technical infrastructure, and the development of clear data governance policies. These measures are crucial for promoting greater teacher buy-in, ensuring the ethical use of AI, and developing sustained engagement with technology-enhanced learning environments.